Time to Volunteer: Changing Determinants and Correlates for Time Contributions to Voluntary Activities - Nadiya Kelle; Corinna Kausmann; Julia Simonson (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2024)
Abstract Volunteers' time contributions have decreased in some European societies, and researchers have sought to understand why. This study aims to uncover the relationship between work-family life changes and changes in individual voluntary behaviour with volunteers' time contributions. To analyse how determinants for volunteer time contributions have changed over time, we draw on cross-sectional data from the German Survey on Volunteering. We apply Poisson regressions for the time period 1999–2019 on nearly 22,000 volunteers. We find a tendency towards decreasing volunteer time contributions. In line with the role-overload theory, longer working hours are increasingly negatively associated with volunteer hours over this period. However, there is no consistent change over time in the association between responsibility for a pre-school child and volunteer hours. Contrary to the theory on the changing nature of volunteering, we do not find conclusive evidence that the shift towards voluntary activities in individually organised, non-hierarchical settings is connected to decreases in volunteer hours.
Keywords: 330; Weekly hours in voluntary activity; Changing volunteer time contributions; Work-family life changes; Individual voluntary behaviour; Gender